An activity of the oil industry and its effects on vegetation coverage in the Amazonas state-Brazil. - Ruiz, Marelis; do Nascimento Noda, Sandra; da Silva, Eliezer; Ladeira, Bruno; Peres de Oliveira, Janiffe (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The objective of this research is to identify effects in vegetation coverage generated by the activity of the oil industry, and obtain the index of environmental degradation for eight counties of the state of Amazonas-Brazil: Coari, Codajás, Anori, Anam í, Caapiranga, Manacapuru, Manaus, and Iranduba. The survey was conducted during the period of dry hydrological. The detection of alterations in vegetation coverage was made possible through the analysis of radar images of satellite RADARSAT-1 and for determination of ID degradation index, were used biological indicators, economic and demographic, using the method of factor analysis with Principal Component decomposition, based on the application of SPSS software. The level of deforestation in the counties as a consequence of oil industry activity was 64.9 km2 of type dense ombrophylous forest; of which Coari has 61 %, Manaus 15%, Anam í 8%, and Codajás 7%. The average ID was 1.09%, the counties with highest ID were Coari and Iranduba with 1.56%, followed by Manaus with 1.48%, the counties with lowest ID were Anori with 0.17% and Caapiranga with 0.6%. By 2008, 97% of the deforested area of the Coari County had been reforested (Petroleum Province of Urucu).